2015
DOI: 10.1007/s40090-015-0054-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some peel extracts on the corrosion behavior of aluminum alloy in alkaline medium

Abstract: Introduction The inhibition performance of three peels, for instance Pisum sativum (PS), Solanum tuberosum (ST), and Citrus reticulata (CR), on aluminum alloy (AA) in 1 M NaOH solution was investigated using weight loss, electrochemical impedance spectroscopy (EIS), linear polarization, and potentiodynamic polarization techniques (Tafel). Results It was found that these three peel extracts exhibit very good performance on AA in alkaline medium. PS exhibited maximum inhibition efficiency (g%) of 94.5 % at 1.5 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 38 publications
(31 reference statements)
0
18
0
Order By: Relevance
“…This result indicated that synthetic EPS may be considered as a mixed-type corrosion inhibitor (Kumar & Yadav, 2016) in the presence of CO 2 gas saturated 3.64% NaCl solution. The maximum displacement in E corr of less than 0.085 V suggests a mixed mode of inhibition (Chaubey, Singh & Quraishi, 2015). Mixed-type corrosion inhibitor retards corrosion rate by suppressing both anodic and cathodic corrosion reactions, typically by adsorbing on a metal surface, forming a protective film to reduce contact of metal surface from the corrosive environment (Myrdal, 2010).…”
Section: Effect Of Concentrationmentioning
confidence: 99%
“…This result indicated that synthetic EPS may be considered as a mixed-type corrosion inhibitor (Kumar & Yadav, 2016) in the presence of CO 2 gas saturated 3.64% NaCl solution. The maximum displacement in E corr of less than 0.085 V suggests a mixed mode of inhibition (Chaubey, Singh & Quraishi, 2015). Mixed-type corrosion inhibitor retards corrosion rate by suppressing both anodic and cathodic corrosion reactions, typically by adsorbing on a metal surface, forming a protective film to reduce contact of metal surface from the corrosive environment (Myrdal, 2010).…”
Section: Effect Of Concentrationmentioning
confidence: 99%
“…These solutions were then tested as inhibitors in the corrosion of 99.95% aluminium in 3% NaCl solution. Apart from this study, 82 all other research work was published on the inhibition of aluminium materials in alkaline (NaOH and KOH) [83][84][85][86][87][88][89][90][91][92][93][94][95][96] and acidic (HCl and H 2 SO 4 ) 9-11,85,93,97-107 solutions ( Table 3).…”
Section: The Corrosion Inhibition Of Plant Extracts Obtained With Solmentioning
confidence: 99%
“…This result indicated that synthetic EPS may be considered as a mixed-type corrosion inhibitor [19] in the presence of CO 2 gas saturated 3.64% NaCl solution. The maximum displacement in E corr of less than 0.085 V suggests a mixed mode of inhibition [20]. Mixed-type corrosion inhibitor retards corrosion rate by suppressing both anodic and cathodic corrosion reactions, typically by adsorbing on a metal surface, forming a protective film to reduce contact of metal surface from the corrosive environment [21].…”
Section: Effect Of Concentrationmentioning
confidence: 99%